FACTORS AFFECTING BEHAVIOR OF FEMALE SPORT TOURISTS PARTICIPATING IN THE MARATHON IN CHONBURI PROVINCE - Jirasanyansakul, Panicha (Dusit Thani College Journal, 2021)
The aim of this research study is two-fold: 1) investigating female sport tourists’ behavior, and 2) exploring the factors affecting behavior of female sport tourists participating in the marathon in Chonburi province. The quantitative method was employed, and data were collected via questionnaires which the value of reliability was .908. The samples of this study were 400 female sport tourists attending the marathon events in Chonburi province. Descriptive statistics were used to describe tourists’ behavior. Additionally, the data were analyzed by the use of Exploratory Factor Analysis (EFA) to extract the factors. The results showed that female sport tourists experienced participating in the marathon 1-3 times with 3-5 people of their families, relatives, or acquaintances. They were staying 2-3 days and their expenses were approximately 3,001-5,000 baht. Importantly, the results revealed that there were four primarily factors affecting female sport tourists’ behavior: 1) Infrastructure and facilities, 2) Competition and service standard, 3) Environmental management of the area, and 4) Marathon image. The factor loading values were 17.838, 17.719, 12.152, and 1.432 respectively. The four-factor structure accounted for 59.142% of the whole variance. This study has shed light on how to support sports events tourism development among female sport tourists.